The Middle Paleolithic Settlement of Croatia - Karavanić, Ivor (Array, 2004)
This paper summarizes the results of research on the Middle Paleolithic sites of Croatia. Northwestern and southern Croatia (Dalmatia), divided by the Dinarid Mountains, provided two different landscapes for the adaptation of Mousterian people and their settlement system. The sites in northwestern Croatia are caves while in Dalmatia, where climate was milder ; open-air sites are more frequent. Caves were usually occupied for short periods of time by mobile groups of people. Neanderthals from northwestern Croatia were successful hunters and they obtained the vast mayority of their dietary protein from meat, largely obtained by hunting. Both in northwestern Croatia and in Dalmatia, Mousterian people modified their lithic technology to exploit effectively local raw material sources. Unfortunately, data related to settlements are rare.